ITIL 4 Direct, Plan and Improve (DPI) your companion to the ITIL 4 managing professional and strategic leader DPI certification - Agutter, Claire (IT Governance Publishing, 2021)
ITIL® 4 Direct, Plan and Improve (DPI) is a study guide designed to help students pass the ITIL® 4 Direct, Plan and Improve module. It provides students with the information they need to pass the exam, and help them become a successful practitioner, with additional guidance throughout which they can lean on once their training and exam are over.
Online resource; title from title details screen (O'Reilly, viewed January 5, 2023)
Keywords: ITIL (Information technology management standard) -- Study guides -- Examinations; Information technology -- Study guides -- Management -- Examinations; Electronic data processing personnel -- Study guides -- Certification -- Examinations; ITIL (Norme); Examens; Guides de l'étudiant; Technologie de l'information; Gestion; Examens; Guides de l'étudiant; examination study guides; Study guides; Guides de l'étudiant